Digital health technologies in Primary Health Care in rural territories: A protocol for scoping review - Vinicius Costa Maia Monteiro; Ísis de Siqueira Silva; Pedro Bezerra Xavier; Felipe Magdiel Bandeira Montenegro; Josemario de Abreu Silva; Severina Alice da Costa Uchoa (PLoS ONE, 2025)
Aim To describe the protocol for a scoping review on digital health technologies in Primary Health Care in rural territories, with a view to evaluating their impact on the attributes of Primary Health Care and identifying barriers and facilitators for its implementation. Background Rural populations face significant barriers in accessing health care, and digital health emerges as a promising strategy to overcome challenges. Nonetheless, there is a gap in the literature regarding the systematic evaluation of the impact of these technologies on rural Primary Health Care, which justifies this scoping review. Method Scoping review protocol, conducted according to the guidelines of the JBI Manual for Evidence Synthesis. It was duly registered in the Open Science Framework platform, with information on the conduct of the study in nine stages, following the PRISMA-ScR. The search strategy includes relevant databases and gray literature to ensure a broad mapping of scientific production on the topic. The analysis of quantitative variables will be carried out by simple descriptive statistics, with absolute and relative frequencies, while qualitative data will undergo thematic content analysis, following the stages of preparation, organization and reporting. Expected results By evaluating the impact of digital technologies on rural Primary Health Care services, as well as identifying barriers and facilitators in their implementation, information is sought to improve access and quality of these services in rural territories through digital health. Conclusion This review will have great practical relevance for managers, public policy makers, health professionals and researchers, as it is intended to map scientific evidence that can support decision-making and the development of strategies for the implementation of digital health in the studied context.